Обґрунтування параметрів технології утилізації вуглекислого газу при підземній газифікації вугілля - Саїк П. Б. (НТУ "ДП", 2024)
Мета. Обґрунтування параметрів технології утилізації вуглекислого газу у складі дуттьової суміші при підземній газифікації вугілля з подальшим встановленням енергетичних характеристик генераторного газу. Purpose. To justify the parameters of the CO₂ utilization technology as part of the blown mixture during underground coal gasification and subsequently determine the energy characteristics of the producer gas.
Substantiation into parameters for the technology of CO₂ utilization in underground coal gasification
Keywords: підземна газифікація вугілля; вуглекислий газ; лабораторні дослідження; теплота згорання; underground coal gasification; carbon dioxide; laboratory experiments; calorific value